2021
DOI: 10.1111/pai.13448
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of factors associated with food protein‐induced enterocolitis syndrome: Birth, infant feeding and food triggers

Abstract: Food protein-induced enterocolitis syndrome (FPIES) is a non-IgEmediated food allergic disorder predominantly affecting infants and children. Despite a poor understanding of its pathophysiology, several large cohort studies and international consensus guidelines have been published. 1 We previously performed a prospective population-based study across Australia examining incidence and clinical phenotype of FPIES. 2 This demonstrated an incidence of 15.4/100 000 in infants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 22 publications
3
20
1
Order By: Relevance
“…[7][8][9][10][11][12] The most frequent culprit food was fish in Greece 13 and Spain 10,14 rice in Australia [15][16][17] and the USA, 18 and oats in Taiwan. 19 Soy is frequently reported as a trigger food by North American, British, Australian and Israeli cohorts 4,17,20,21 and was infrequent in our population. Food habits, geographic origins, genetic factors, microbiota, and other environmental pre-or postnatal factors may explain these differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10][11][12] The most frequent culprit food was fish in Greece 13 and Spain 10,14 rice in Australia [15][16][17] and the USA, 18 and oats in Taiwan. 19 Soy is frequently reported as a trigger food by North American, British, Australian and Israeli cohorts 4,17,20,21 and was infrequent in our population. Food habits, geographic origins, genetic factors, microbiota, and other environmental pre-or postnatal factors may explain these differences.…”
Section: Discussionmentioning
confidence: 99%
“…The age at resolution was based on the day of performance of an OFC and thus may be overestimated. Previous studies suggested that the later age of tolerance relates to the ingestion of seafood products 6,9,17,22 and may occur more frequently in cases of multiple FPIES. 6 Resolution of FPIES to fish is around 18.8% to 57.0% of cases between 3 to 4.5 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 A recent cohort study from Australia over the last decade also found a 4-month delay among their patients. 8 In addition to a prolonged length to diagnosis, patients may also experience a number of FPIES episodes prior to diagnosis. Blackman et al found that 32% of patients had up to four FPIES episodes prior to diagnosis and Mehr et al who found that 20% of patients had up to four episodes prior to diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The present study enrolled 21 patients with EY-FPIES (1) diagnosed by positive oral food challenge (OFC) tests at our hospital between April 2018 and April 2021 who (2) subsequently underwent OFC to evaluate tolerance acquisition (re-OFC) at least once. The open OFC was performed by ingestion of a single dose once or three divided doses every 30 minutes.…”
mentioning
confidence: 99%